Pengaruh Motivasi Kerja dan Kompensasi terhadap Kinerja Pegawai di Dinas Perindustrian dan Perdagangan Kabupaten Tapanuli Tengah - Rasmin Simbolon (Neolectura, 2021)
This study aims to determine the effect of work motivation and compensation on performance, either partially or collectively. Organizations expect Human Resources to perform well to realize their vision, mission and goals. A person's performance can be maximized if supported by work motivation and by providing appropriate compensation and will perform poorly if work motivation and compensation are not available. The Performance Accountability Report at the Central Tapanuli Regency Office of Industry and Trade shows the low performance achievements over the past five years are the basis of this research. The type of research design carried out is quantitative research with a descriptive approach based on surveys. Sampling techniques through questionnaires and documents with a population of 34 people. Data analysis techniques use multiple models of linear regression equations. The results of the research analysis showed: Work motivation has a significant and positive effect on the performance of employees in the Office of Industry and Trade of Central Tapanuli Regency; Compensation has no significant effect, but is positive to the performance of employees in the Office of Industry and Trade of Central Tapanuli Regency; Work motivation and compensation together have a significant and positive effect on the performance of employees in the Office of Industry and Trade of Central Tapanuli Regency. The variable that affects performance the most is Work Motivation with a Standardized Coefficientsvalue of 0.682.